Gender, poverty, and inequality: a brief history of feminist contributions in the field of international development - Kabeer, Naila (Gender & Development, 2015)
This paper provides a brief history of feminist contributions to the analysis of gender, poverty, and inequality in the field of international development. It draws out the continuous threads running through these contributions over the years, as the focus has moved from micro-level analysis to a concern with macro-level forces. It concludes with a brief note on some of the confusions and conflations that continue to bedevil attempts to explore the relationship between gender, poverty, and inequality.
Keywords: approches et analyses; cours; discipline; développement international; histoire et politique; intersectionnalité; inégalités; justice sociale; pauvreté; pol4022; premier cycle; ressource en ligne; science politique; science politique et droit; sciences de la gestion; systèmes d'oppressions; thématiques; économie

The SAGE handbook of feminist theory - Evans, Mary (SAGE reference, 2014)
At no point in recorded history has there been an absence of intense, and heated, discussion about the subject of how to conduct relations between women and men. This Handbook provides a comprehensive guide to these omnipresent issues and debates, mapping the present and future of thinking about feminist theory. The chapters gathered here present the state of the art in scholarship in the field, covering: Epistemology and marginality; Literary, visual and cultural representations; Sexuality; Macro and microeconomics of gender; Conflict and peace. The most important consensus in this volume is that a central organizing tenet of feminism is its willingness to examine the ways in which gender and relations between women and men have been (and are) organized. The authors bring a shared commitment to the critical appraisal of gender relations, as well as a recognition that to think ‘theoretically’ is not to detach concerns from lived experience but to extend the possibilities of understanding. With this focus on theory and theorizing about the world in which we live, this Handbook asks us, across all disciplines and situations, to abandon our taken-for-granted assumptions about the world and interrogate both the origin and the implications of our ideas about gender relations and feminism. It is an essential reference work for advanced students and academics not only of feminist theory, but of gender and sexuality across the humanities and social sciences.
Le chapitre Boyle, K. (2014). Feminism and pornography (pp. 215-231) a été donné en lecture au cours SEX1911.
Keywords: approches et analyses; corps; cours; discipline; har4600; histoire et politique; intersectionnalité; outils; ouvrages de références; philosophie; phénoménologie; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences de la gestion; sciences humaines; sciences sociales; sex1911; thématiques; violences; économie; épistémologie; études féministes